Neurodegenerative disease biomarkers Aβ1–40, Aβ1–42, tau, and p‐tau181 in the vervet monkey cerebrospinal fluid: Relation to normal aging, genetic influences, and cerebral amyloid angiopathy. Issue 2 (13th January 2018) - Chen, Jason A.; Fears, Scott C.; Jasinska, Anna J.; Huang, Alden; Al‐Sharif, Noor B.; Scheibel, Kevin E.; Dyer, Thomas D.; Fagan, Anne M.; Blangero, John; Woods, Roger; Jorgensen, Matthew J.; Kaplan, Jay R.; et al.
Abstract: Background: The Caribbean vervet monkey ( Chlorocebus aethiops sabaeus ) is a potentially valuable animal model of neurodegenerative disease. However, the trajectory of aging in vervets and its relationship to human disease is incompletely understood. Methods: To characterize biomarkers associated with neurodegeneration, we measured cerebrospinal fluid (CSF) concentrations of Aβ1–40, Aβ1–42, total tau, and p‐tau181 in 329 members of a multigenerational pedigree. Linkage and genome‐wide association were used to elucidate a genetic contribution to these traits. Results: Aβ1–40 concentrations were significantly correlated with age, brain total surface area, and gray matter thickness. Levels of p‐tau181 were associated with cerebral volume and brain total surface area. Among the measured analytes, only CSF Aβ1–40 was heritable. No significant linkage (LOD > 3.3) was found, though suggestive linkage was highlighted on chromosomes 4 and 12. Genome‐wide association identified a suggestive locus near the chromosome 4 linkage peak. Conclusions: Overall, these results support the vervet as a non‐human primate model of amyloid‐related neurodegeneration, such as Alzheimer's disease and cerebral amyloid angiopathy, and highlight Aβ1–40 and p‐tau181 as potentially valuable biomarkers of these processes. Abstract : The Caribbean vervet monkey (Chlorocebus aethiops sabaeus) is a potentially valuable animal model of neurodegenerative disease. We identified correlations with aging and brain atrophy with Aβ1–40 and p‐tau181 in a vervet pedigree and further identified heritability in these measurements, pointing towards applicability of the vervet model.